2019
DOI: 10.1177/1753425919861774
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 regulates pulmonary fibrosis via modulating IL-13 expression in macrophages

Abstract: Idiopathic pulmonary fibrosis is a progressive interstitial pneumonia characterised by fibroblast accumulation, collagen deposition and extracellular matrix (ECM) remodelling. It was reported that Akt1 mediated idiopathic pulmonary fibrosis progression through regulating the apoptosis of alveolar macrophage, while its effect on macrophage-produced cytokines remains largely unknown. In the present study, we first examined the phosphorylation of Akt1 in lung sections from idiopathic pulmonary fibrosis patients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Akt1, a pro‐survival kinase, is known to mediate mitochondrial H2O2 generation. Akt1 activation is strongly associated with regulating survival and many fibrotic remodelling processes . The phosphorylation level of Akt is associated with HSC proliferation and collagen I expression .…”
Section: Discussionmentioning
confidence: 99%
“…Akt1, a pro‐survival kinase, is known to mediate mitochondrial H2O2 generation. Akt1 activation is strongly associated with regulating survival and many fibrotic remodelling processes . The phosphorylation level of Akt is associated with HSC proliferation and collagen I expression .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that IL-13 produced by M2 macrophages also plays a key role in the homeostasis control of normal lungs and the pathogenesis of pulmonary fibrosis. AKT1 regulates pulmonary fibrosis by inducing M2 macrophages to produce IL-13, suggesting that targeting AKT1 blocks the fibrotic process of IPF 95 . The O subclasses of the Forkhead box (FOXO) family, such as FOXO1, FOXO3, and FOXO4, are directly phosphorylated by AKT, causing them to be exported to the cytoplasm and degraded through the ubiquitin-proteasome pathway.…”
Section: Pi3k/akt Signaling In Different Development Stage Of Ipfmentioning
confidence: 99%
“…A previous study indicated that m 6 A mRNA methylation regulates AKT1 activity, which promotes the tumorigenicity of endometrial cancer (46). Protein kinase B (AKT) is a pleckstrin homology (PH) domain comprising a serine threonine kinase (53). AKT1 is an important isoform of AKT, which acts as a vital subtype and is closely related to many types of human tumors (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%